(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores the challenges facing multilateral institutions in tackling global issues like climate change and cybersecurity. It examines the role of U.S. engagement and how shifts in U.S. foreign policy impact global governance. Highlighting the need for reform—through transparency, flexibility, and regional collaboration—the article argues that effective U.S. leadership is essential to strengthen these institutions. Renewed U.S. commitment to multilateralism can help build a cooperative, resilient international system equipped for 21st-century challenges.